Demographic differences matter on job outcomes: psychological contract’s mediating role - Ali Ender Altunoğlu (Business, Management and Economics Engineering, 2022)
Purpose – Drawing upon prior researches on the social exchange theory, we examine the effect of employee demographic variables on psychological contract fulfillment, which eventually influences employee’s job satisfaction, intention to leave, organizational citizenship behavior, cynicism, and task performance.